Pengaruh gaya kepemimpinan transformasional terhadap kinerja guru (SMK Negeri 2 Kerinci) - Randa Krismon; Zulfina Adriani; Ratnawati Ratnawati (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
This study aims to determine the effect of transformational leadership style on teacher performance at SMKN 2 Kerinci. This research uses quantitative research. The population in this study were all teachers of SMKN 2 Kerinci totaling 60 teachers. The sampling method used the total sampling method. The number of samples in this study was 60 teachers. Methods of data collection using a questionnaire or questionnaire and measured with a Likert scale. Data testing techniques used in this study include instrument testing (validity test, reliability test), data analysis methods consist of descriptive analysis and simple linear regression analysis. Hypothesis testing consists of t test, and coefficient of determination test (R2) with the help of SPSS V 24 application. The results of this study show that Transformational Leadership Style has a positive and significant effect on Teacher Performance at SMK Negeri 2 Kerinci.